Dynamic complex-to-complex transformations of heterobimetallic systems influence the cage structure or spin state of iron(II) ions - Hardy, Matthias; Struch, Niklas; Holstein, Julian J.; Schnakenburg, Gregor; Wagner, Norbert; Engeser, Marianne; Beck, Johannes; Clever, Guido H.; Lützen, Arne (Technische Universität Dortmund, 2019)
Two new heterobimetallic cages, atrigonal-bipyr-amidal and acubic one, were assembled from the same mononuclear metalloligand by adopting the molecular library approach,using iron(II) and palladium(II) building blocks. The ligand system was designed to readily assemble through subcomponent self-assembly. It allowed the introduction of steric strain at the iron(II) centres, which stabilizes its para-magnetic high-spin state.This steric strain was utilized to drive dynamic complex-to-complex transformations with both the metalloligand and heterobimetallic cages. Addition of steri-cally less crowded subcomponents as achemical stimulus transformed all complexes to their previously reported low-spin analogues.The metalloligand and bipyramid incorporated the new building blockmore readily than the cubic cage, probably because the geometric structure of the sterically crowded metalloligand favours the cube formation. Further-more it was possible to provokestructural transformations upon addition of more favourable chelating ligands,converting the cubic structures into bipyramidal ones.
Angewandte Chemie. International Edition;Vol. 59. 2020, Issue 8, pp 3195 –3200
Keywords: Self assembly; heterobimetallic cages; complex to complex transformation; spin state of iron(II) ions; 540